Maksim Percakapan dalam Program Acara I-Talk di Insert Live - Siti Khodijah; Mardiningsih Mardiningsih; Badriyah Wulandari (CV. Rayyan Dwi Bharata, 2024)
This study aims to describe the form and function of conversational maxims in the I-Talk program on Insert Live. The inappropriateness of the speaker's speech in responding to the presenter's speech and the lack of communication strategies carried out by the presenter in talking to the speaker are the background for the researcher to choose the speech between Maria Christy and Amanda Caesa in the I-Talk program to be studied. This study uses a descriptive research type with a qualitative approach, because it can explain simply and clearly based on the focus of the study. The data in this study are the speech between Maria Christy and Amanda Caesa in the I-Talk program on Insert Live which contain conversational maxims, and the data sources are obtained from the I-Talk program on the Insert Live platform. The data collection technique in this study uses the free listening technique and the note-taking technique. The data analysis technique in this study uses data reduction, data presentation, and conclusion drawing techniques. The results of this study are the form and function of conversational maxims in the I-Talk program. The forms of conversational maxims found are the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of implementation. The conversational maxim functions found are assertive, directive, and expressive functions. The maxim of quantity is the most frequently found in this study, because Maria Christy and Amanda Caesa provide informative speech or information and do not exceed what is needed. The assertive function is the most frequently found in this study, because Maria Christy and Amanda Caesa provide speech that functions to state, ask, and explain as an effective communication strategy between speakers and conversation partners in the I-Talk event on Insert Live.